Development of a Digital Curation Maturity Model and Indicators Including Weights for Measuring Digital Transformation Outcomes - Kim, Seonghun; Park, Jinho (International Journal of Knowledge Content Development & Technology, 2025)
Information management institutions consider digital curation as a crucial area, and achieving digital transformation using the latest technologies is highly important. However, evaluation models for the maturity of digital curation and its continuous development have been scarce. Hence, this study developed a digital curation maturity model and indicators for measuring digital transformation outcomes. Weights were assigned to each indicator to allow for practical application during evaluations. This study identified 16 medium categories under 5 main categories, along with 40 subcategories. It also found 117 indicators and calculated weights for each main category and subcategory. The digital transformation maturity assessment model’s most basic function is to assess the current state of the organization, providing a means for control and suggesting actions for the future. The findings can be used to conduct a systematic evaluation of digital curation maturity, contributing to the continuous development of information management.